"Deciphering the enigmatic role of gamma-aminobutyric acid (GABA) in plants Synthesis, transport, regulation, signaling, and biological roles in interaction with growth regulators and abiotic stresses." - Ahmad, Saif (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.